2015
DOI: 10.1093/cercor/bhv024
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Left Versus Right Anterior Temporal Lobes in Conceptual Knowledge: An ALE Meta-analysis of 97 Functional Neuroimaging Studies

Abstract: The roles of the right and left anterior temporal lobes (ATLs) in conceptual knowledge are a source of debate between 4 conflicting accounts. Possible ATL specializations include: (1) Processing of verbal versus non-verbal inputs; (2) the involvement of word retrieval; and (3) the social content of the stimuli. Conversely, the “hub-and-spoke” account holds that both ATLs form a bilateral functionally unified system. Using activation likelihood estimation (ALE) to compare the probability of left and right ATL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

44
236
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 282 publications
(282 citation statements)
references
References 115 publications
(278 reference statements)
44
236
2
Order By: Relevance
“…Neuropsychological studies and neuroanatomically constrained computational models also implicate the lateral ATL in semantically mediated speech production (50,53). This role is consistent with the view that (i) as a result of the convergence of multiple white-matter tracts and connections, the ATL region as a whole acts as a representational system and (ii) there are graded specializations in different parts of this system, as a consequence of systematic variations in structural connectivity across the region (54,55).…”
Section: Discussionsupporting
confidence: 76%
“…Neuropsychological studies and neuroanatomically constrained computational models also implicate the lateral ATL in semantically mediated speech production (50,53). This role is consistent with the view that (i) as a result of the convergence of multiple white-matter tracts and connections, the ATL region as a whole acts as a representational system and (ii) there are graded specializations in different parts of this system, as a consequence of systematic variations in structural connectivity across the region (54,55).…”
Section: Discussionsupporting
confidence: 76%
“…This finding adds to a growing body of literature comparing processing in the left vs. right ATL. A seminal magnetoencephalography study of semantic processing across modalities, as well as a recent largescale meta-analysis of functional imaging studies (37,39), found that ATL activation for written words or speech production is strongly left-lateralized, whereas other forms of semantic tasks (pictures, auditory words, and auditory sounds) show bilateral ATL engagement (see also ref. 19).…”
Section: Discussionmentioning
confidence: 99%
“…Frontal regions are engaged in unification operations (15), integrating lexical units into the larger context. Anterior temporal cortex is associated with conceptual object representations (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that rhythmic activity in the alpha frequency range (8-12 Hz) propagates from temporal cortical areas to frontal cortical areas, and that beta frequency rhythmic activity (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) propagates in the opposite direction. These results indicate the functional relevance of rhythmic directed interactions during language processing, where interactions between areas are supported by different frequency bands, depending on the direction of the interaction.…”
mentioning
confidence: 95%